2019
DOI: 10.1002/tox.22699
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the toxic effects of titanium dioxide nanoparticles in blood, liver, muscles, and brain of a Neotropical detritivorous fish

Abstract: The toxicity of titanium dioxide nanoparticles (TiO 2 -NP) in the blood, liver, muscle, and brain of a Neotropical detritivorous fish, Prochilodus lineatus, was tested. Juvenile fish were exposed to 0, 1, 5, 10, and 50 mg L −1 of TiO 2 -NP for 48 hours (acute exposure) or 14 days (subchronic exposure) to evaluate changes in hematology, red blood cell (RBC) genotoxicity/mutagenicity, liver function (reactive oxygen species (ROS) production, antioxidant responses, detoxification, and histopathology), acetylcholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 57 publications
1
23
0
3
Order By: Relevance
“…In the present study, no neurological disturbances of the cholinergic system were found in the brain after IP injection of TiO 2 NPs and BP-3, isolated or in mixture, for 3 and 7 days. In the same direction, several studies with freshwater fish reported no alterations in the AChE activity in the brain after waterborne exposure to TiO 2 NPs [46,[80][81][82][83]. On the contrary, waterborne exposure of the freshwater fish Carassius auratus to 200 µg L −1 of BP-3 promoted the increase in the activity of AChE [84].…”
Section: Neurotoxicitymentioning
confidence: 92%
See 1 more Smart Citation
“…In the present study, no neurological disturbances of the cholinergic system were found in the brain after IP injection of TiO 2 NPs and BP-3, isolated or in mixture, for 3 and 7 days. In the same direction, several studies with freshwater fish reported no alterations in the AChE activity in the brain after waterborne exposure to TiO 2 NPs [46,[80][81][82][83]. On the contrary, waterborne exposure of the freshwater fish Carassius auratus to 200 µg L −1 of BP-3 promoted the increase in the activity of AChE [84].…”
Section: Neurotoxicitymentioning
confidence: 92%
“…Interestingly, some authors found a reduction in AChE activity in fish muscle after exposure to TiO 2 NPs while no alteration was found in the brain [80,82]. This suggests that the neurotoxic action of TiO 2 NPs does not affect brain directly but may be related with alterations of the metabolic processes on which the nervous system is specifically dependent.…”
Section: Neurotoxicitymentioning
confidence: 99%
“…Carmo et al reported the reduction of hemoglobin content and white and red blood cells in freshwater fish after exposure to TiO 2 NPs [15]. They treated Juvenile fish with various amounts of TiO 2 NPs (1-50 mg/L) for 48 h or 14 days as acute and subchronic exposures, respectively.…”
Section: Effects Of Tio 2 Nps On Aquatic Speciesmentioning
confidence: 99%
“…It was also observed that the NPs demonstrated potential for increasing energy expenditure by affecting the immune system, thereby decreasing the ability of the fish to avoid predators and fight pathogens. In addition to the toxic effect of TiO 2 NPs on blood cells, they may also be distributed to several organs through the blood stream, thereby modifying cellular metabolism and could possibly lead to some form of physiological imbalance of these affected organs [5,15,113]. Furthermore, exposure to TiO 2 NPs may cause damages to liver tissues of aquatic species, such as the presence of disordered cells, apoptotic nuclei, and foci with lipid accumulation [114].…”
Section: Effects Of Tio 2 Nps On Aquatic Speciesmentioning
confidence: 99%
See 1 more Smart Citation